MYB103 is required for FERULATE‐5‐HYDROXYLASE expression and syringyl lignin biosynthesis in Arabidopsis stems. (19th October 2012) - Öhman, David; Demedts, Brecht; Kumar, Manoj; Gerber, Lorenz; Gorzsás, András; Goeminne, Geert; Hedenström, Mattias; Ellis, Brian; Boerjan, Wout; Sundberg, Björn
Summary: The transcription factor MYB103 was previously identified as a member of the transcriptional network regulating secondary wall biosynthesis in xylem tissues of Arabidopsis, and was proposed to act on cellulose biosynthesis. It is a direct transcriptional target of the transcription factor SECONDARY WALL ASSOCIATED NAC DOMAIN PROTEIN 1 (SND1), and 35S‐driven dominant repression or over‐expression of MYB103 modifies secondary wall thickness. We identified two myb103 T‐DNA insertion mutants and chemically characterized their lignocellulose by pyrolysis/GC/MS, 2D NMR, FT‐IR microspectroscopy and wet chemistry. The mutants developed normally but exhibited a 70–75% decrease in syringyl (S) lignin. The level of guaiacyl (G) lignin was co‐ordinately increased, so that total Klason lignin was not affected. The transcript abundance of FERULATE‐5 ‐ HYDROXYLASE ( F5H ), the key gene in biosynthesis of S lignin, was strongly decreased in the myb103 mutants, and the metabolomes of the myb103 mutant and an F5H null mutant were very similar. Other than modification of the lignin S to G ratio, there were only very minor changes in the composition of secondary cell‐wall polymers in the inflorescence stem. In conclusion, we demonstrate that F5H expression and hence biosynthesis of S lignin are dependent on MYB103.